THE IMPORTANCE OF SPORT IN THE PHYSICAL AND SOCIAL DEVELOPMENT OF CHILDREN AND ADOLESCENTS - Mello, Luis Eduardo (LUMEN ET VIRTUS, 2024)
Sport participation during childhood and adolescence plays a crucial role in promoting physical health, psychological well-being, and social development. Scientific evidence consistently demonstrates that regular engagement in sports contributes to improved motor skills, physical fitness, emotional regulation, and social competence among young people. Beyond physical benefits, sport provides a structured environment for learning cooperation, discipline, and resilience, supporting the holistic development of children and adolescents. This article discusses the importance of sport as a developmental tool and reflects on pedagogical strategies used in educational settings to maximize its physical and social benefits.